Candombe do Açude entre a tradição e a exposição - Cristiano A Ferreira Trindade (2011)
The Candombe is a ritual, originated during the colonial period to praise Nossa Senhora do Rosário and the ancestors, still performed by the descendants of the slaves at the Cipó Farm assembled in the Açude Community, located in Jaboticatubas Municipality, Minas Gerais state. The ritual characterized throughout history for keeping itself distant from public sphere, however, in the case of Candombe do Açude, it has been required by artists and researchers to participate in documentaries, commercial recordings of audio, video and to present itself outside the context of the community, which has brought wider publicity to the ritual. The objective of the present paper is to observe the realization of the ritual in its original context, compare it to the ritual aired in the media, and to check possible transformations in its performance, as well as in its relation to the socio-political context. The political place of the main actors involved, media, State, afrodescendant culture, was situated historically. Subsequently, its been developed a carachterization of Candombe do Açude, its relation with tourism and a evaluation of its participation in the media products selected.